Autumn migrating passerines at a desert edge: Do birds depart for migration after reaching a threshold fuel load or vary it according to the rate of fuel deposition? - Zinßmeister, Daniela; Troupin, David; Sapir, Nir (Frontiers in Ecology and Evolution, 2022)
Fuel deposition rate is predicted to determine departure fuel load during stopover in two models of optimal behavior of migrating birds. Yet, near ecological barriers, such as wide deserts, birds may switch to a different strategy of departing with just enough fuel to enable the long cross-barrier flight, thus reaching a threshold of fuel load regardless of the rate of fuel deposition. To test these predictions we studied autumn migrating Red-backed Shrikes (Lanius collurio) before they departed for a 2,000 km journey across the Sahara Desert. The body mass of fourteen individuals was measured on a daily basis throughout their stopover using field deployed scales while being tracked by the ATLAS biotelemetry system in the Hula Valley, Israel. Statistical analysis found that the natural log of departure fuel load was positively related to both the capture fuel load and the fuel deposition rate. Hence, the results of this analysis suggest that bird condition at departure depended on the rate of fuel deposition, as predicted by models of time-minimization migration and the minimization of the total energy cost of migration. Departure fuel load and stopover duration were negatively related to each other as birds that remained for a long time in stopover departed with relatively low fuel loads. These findings suggest that even near a wide ecological barrier, departure fuel load is sensitive to the rate of fuel deposition, especially at lower values of fuel deposition rate. Birds that were able to accumulate fuel at higher rates showed a nearly constant departure fuel load and as such we could not exclude the possibility that the birds were trying to reach a certain threshold of fuel stores. Randomized 1,000 repeats of the aforementioned correlation suggest that the correlation between fuel deposition rate and the log of departure fuel load is valid and does not represent a spurious result. Following bird migration simulation using the program Flight, we conclude that fuel loads allowed most individual to accomplish the journey across the desert. Our findings suggest high between-individual variation in stopover parameters with likely consequences for bird migration performance and survival.